2022
DOI: 10.1136/bmjopen-2020-048207
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of paediatric inpatient experience: retrospective analysis of casemix factors for the Alberta Paediatric Inpatient Experience Survey in Alberta, Canada

Abstract: ObjectiveIn Alberta, the Alberta Paediatric Inpatient Experience Survey (APIES) is used as a proxy-reported measure of paediatric experience. To our knowledge, the influence of casemix factors on patient experience as measured by paediatric patient experience surveys have not been reported within Canadian paediatric samples. In this paper, we sought to determine the patient and respondent factors associated with paediatric inpatient experiences in Alberta, Canada.DesignRetrospective analysis of patient experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…With respect to the drivers of overall experience among adults, we observed, using survey data linked with inpatient records, that younger adults, males, those with higher levels of education, those born in Canada, patients admitted to hospital on an urgent basis, those not having a primary care provider as the attending physician, and not being discharged home reported lower ratings of overall experience [33]. Among parents of hospitalized children, we observed similar results; that younger respondents, those with poorer parent-reported child health, higher levels of education, and children not treated in stand-alone pediatric hospitals reported lower odds of reporting a "top box" overall rating [34].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…With respect to the drivers of overall experience among adults, we observed, using survey data linked with inpatient records, that younger adults, males, those with higher levels of education, those born in Canada, patients admitted to hospital on an urgent basis, those not having a primary care provider as the attending physician, and not being discharged home reported lower ratings of overall experience [33]. Among parents of hospitalized children, we observed similar results; that younger respondents, those with poorer parent-reported child health, higher levels of education, and children not treated in stand-alone pediatric hospitals reported lower odds of reporting a "top box" overall rating [34].…”
Section: Resultssupporting
confidence: 66%
“…Drivers of overall experience (child) [34] Determine the patient and respondent factors associated with pediatric inpatient experiences.…”
Section: Cpes-ic Dadmentioning
confidence: 99%
“…This research should focus not only on the fidelity of the protocol for this group but also on the content and evaluative tone. Recent research showed that parents with lower education are likely to provide a less critical appraisal of their child's hospitalization experience when responding to closed‐ended survey questions 30 . If this pattern extends to open‐ended responses, then our study may underestimate the positivity of narrative responses that can be expected in samples that include a larger proportion of participants with lower educational attainment.…”
Section: Discussionmentioning
confidence: 67%
“…Recent research showed that parents with lower education are likely to provide a less critical appraisal of their child's hospitalization experience when responding to closed-ended survey questions. 30 If this pat-…”
Section: Limitationsmentioning
confidence: 99%